Studi Laporan Kasus Reaksi yang Merugikan Pasca Vaksinasi Covid-19: Narrative Review - Ainina Al Shadrina; Kusnandar Anggadiredja (Acta Pharmaceutica Indonesia, 2022)
The accelerated Covid-19 vaccines’ emergency use authorization raises many questions regarding the safety and effectiveness of the vaccine due to the short duration of the pre-marketing clinical trial phase. In terms of vaccine safety, longer studies are needed, especially to see if there are long-term effects or unusual effects that were not detected during pre-marketing clinical trials. This study aims to summarize and assess the adverse reactions that occur after the administration of the Covid-19 vaccine that has obtained approval for emergency use. The search for case reports was carried out in the PubMed database with the keyword "case report on post covid-19 vaccination". Screening for duplication and assessment of each study was also carried out. The case findings obtained were then grouped based on patient demographics, type of vaccine, post-vaccination effects, medical interventions, and end results. There were 118 case reports of adverse effects after the Covid-19 vaccination. The most widely used type of vaccine was mRNA vaccine (76 cases; 64.41%) and the least was inactivated virus vaccine (3 cases; 2.54%). The most reported cases were those affecting the cardiovascular/circulatory/lymphatic system (42 cases; 35.59%) and the least were those affecting the respiratory system (1 case; 0.85%). A total of 89 cases were resolved (89 cases; 75.42%), 4 cases (3.39%) with disability and 2 cases (1.69%) of death were reported. The medical interventions used were mostly inflammatory response-related interventions.